2015
DOI: 10.1136/bmj.h5639
|View full text |Cite
|
Sign up to set email alerts
|

Risk of postoperative acute kidney injury in patients undergoing orthopaedic surgery--development and validation of a risk score and effect of acute kidney injury on survival: observational cohort study

Abstract: Study queStionWhat is the predicted risk of acute kidney injury after orthopaedic surgery and does it affect short term and long term survival? MethodSThe cohort comprised adults resident in the National Health Service Tayside region of Scotland who underwent orthopaedic surgery from 1 January 2005 to 31 December 2011. The model was developed in 6220 patients (two hospitals) and externally validated in 4395 patients from a third hospital. Several preoperative variables were selected for candidate predictors, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
127
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(149 citation statements)
references
References 42 publications
11
127
3
Order By: Relevance
“…Previous studies have also noted effect modification by baseline function12, 32, 33 and a diminishing role of AKI after hospital discharge 34, 35. This analysis now shows that the diminishing role of AKI continues for up to 1 year after AKI and is present at all levels of baseline kidney function.…”
Section: Discussionsupporting
confidence: 68%
“…Previous studies have also noted effect modification by baseline function12, 32, 33 and a diminishing role of AKI after hospital discharge 34, 35. This analysis now shows that the diminishing role of AKI continues for up to 1 year after AKI and is present at all levels of baseline kidney function.…”
Section: Discussionsupporting
confidence: 68%
“…Bell et al found women to be 50% less likely to develop AKI after undergoing orthopedic surgery. 30 Similarly, in a study of postoperative general surgery patients, women were noted to be 40% less likely to develop AKI. 31 Although the complete mechanism is not well understood, animal models suggest that estrogen might be responsible for protecting the kidney from ischemic injury.…”
Section: Discussionmentioning
confidence: 95%
“…In AKI predictive modeling, logistic regression with backward or forward selection (wrapper method) is often used to select a subset of features for model building 7 ; chi-squared test (filter) 8 , random forest (embedded) 9 , and gradient boosting machine (embedded) 10 have also been applied to illustrate the feature importance and ranking in AKI prediction. With the increasing variety of feature selection methods and their frequent utilization in the health informatics research community, new questions arise, namely there is no systematic way to choose the most appropriate feature selection method for a given domain and problem, which often depends on two aspects 11 : (a) the stability of FS ranking with respect to different samples, and (b) the prediction accuracy of FS subset effectively representing the entire data.…”
Section: Introductionmentioning
confidence: 99%